Dermoscopy of Non-Melanocytic Skin Tumors: A Descriptive Study in a Tertiary Care Hospital - Thapa, Deeptara Pathak; Bhandari, Sajana; Adhikari, Harihar; Joshi, Sammi (Nepal Journal of Dermatology, Venereology & Leprology, 2022)
Introduction: Dermoscopy is a non-invasive technique that enhances visualization of morphological lesions invisible to naked eye examination and aids in clinical diagnosis. We study its role in non-melanocytic skin tumors. Objectives: The purpose of this study was to evaluate and compare the dermoscopic features of non-melanocyte skin tumors of skin Materials and Methods: A cross-sectional hospital-based study including patients clinically diagnosed as non-melanocytic epidermal tumors was conducted. All dermoscopic findings were studied using a handheld pocket dermoscope (Dermlite DL1) and recorded in a preset proforma. Results: A total of 100 patients were enrolled in the study with mean age of 37 (+/-18.34). There were 56 % females. The face was the commonest site of involvement (56%). Seborrheic keratosis was the commonest clinical diagnosis (55%), followed by pyogenic granuloma 8%, cherry angioma 7%, haemangioma 6%, basal cell carcinoma 5%, achrochordons 4%, xanthelasma, and sebaceous hyperplasia in 3% each. Squamous cell carcinoma and actinic keratosis were seen in 2% each; Angiokeratoma, Bowens disease, stetocytoma multiplex, syringoma, and neurofibroma were all found in 1% of the patients. In dermoscopy, vascular changes were seen in 41% patients, which appeared as regular in 56.1% and rest 43.9% as irregular. Non-vascular changes were seen in 68%. Dermoscopic findings of vascular and non-vascular changes were statistically significantly associated with various types of non-melanocytic epidermal tumors (P <0.05). Conclusion: Our study shows histopathological correlation with the existing dermoscopic characteristics increases the diagnostic accuracy of various non-melanocytic tumors. However, more studies are warranted to statistically prove its utility.